Mammalian Target of Rapamycin Inhibition in Trypanosoma cruzi-Infected Macrophages Leads to an Intracellular Profile That Is Detrimental for Infection - Rojas Márquez, Jorge David; Ana, Yamile; Baigorrí, Ruth Eliana; Stempin, Cinthia Carolina; Cerban, Fabio Marcelo (Frontiers in Immunology, 2018)
The causative agent of Chagas’ disease, Trypanosoma cruzi, affects approximately 10 million people living mainly in Latin America, with macrophages being one of the first cellular actors confronting the invasion during T. cruzi infection and their function depending on their proper activation and polarization into distinct M1 and M2 subtypes. Macrophage polarization is thought to be regulated not only by cytokines and growth factors but also by environmental signals. The metabolic checkpoint kinase mammalian target of rapamycin (mTOR)-mediated sensing of environmental and metabolic cues influences macrophage polarization in a complex and as of yet incompletely understood manner. Here, we studied the role of the mTOR pathway in macrophages during T. cruzi infection. We demonstrated that the parasite activated mTOR, which was beneficial for its replication since inhibition of mTOR in macrophages by different inhibitors decreased parasite replication. Moreover, in rapamycin pretreated and infected macrophages, we observed a decreased arginase activity and expression, reduced IL-10 and increased interleukin-12 production, compared to control infected macrophages treated with DMSO. Surprisingly, we also found a reduced iNOS activity and expression in these macrophages. Therefore, we investigated possible alternative mechanisms involved in controlling parasite replication in rapamycin pretreated and infected macrophages. Although, cytoplasmic ROS and the enzyme indoleamine 2, 3-dioxygenase (IDO) were not involved, we observed a significant increase in IL-6, TNF-α, and IL-1β production. Taking into account that IL-1β is produced by activation of the cytoplasmic receptor NLRP3, which is one of the main components of the inflammasome, we evaluated NLRP3 expression during mTOR inhibition and T. cruzi infection. We observed that rapamycin-pretreated and infected macrophages showed a significant increase in NLRP3 expression and produced higher levels of mitochondrial ROS (mtROS) compared with control cells. Moreover, inhibition of mtROS production partially reversed the effect of rapamycin on parasite replication, with there being a significant increase in parasite load in rapamycin pretreated and infected macrophages from NLRP3 KO mice compared to wild-type control cells. Our findings strongly suggest that mTOR inhibition during T. cruzi infection induces NLRP3 inflammasome activation and mtROS production, resulting in an inflammatory-like macrophage profile that controls T. cruzi replication.